(untitled) (Journal of Applied Learning and Teaching, 2024)
Helen Sword, Professor Emeritus at the University of Auckland, New Zealand, specialises in modernist poetry and academic writing. In 2023, she was elected a Fellow of the Royal Society Te Apārangi for her ground-breaking scholarship on academic writing, which skillfully integrates theory and practice. Sword has inspired countless writers with her insightful and practical guides to becoming an accomplished and stylish academic writer, even within the constraints of academic conventions. Her notable books on academic writing include The writer’s diet (2016a; first published in 2007), Stylish academic writing (2012a), Air & light & time & space: How successful academics write (2017), and Writing with pleasure (2023). In this multifaceted interview, Sword discusses her journey to becoming an expert on academic writing, the current state of academic prose, and strategies for writing more stylishly and pleasurably. She shares her unorthodox research methods, which draw upon her background in literary studies and poetry, and emphasises the importance of the behavioural, artisanal, social, and emotional dimensions of writing. Sword also addresses the challenges posed by academic conventions and the role of generative AI, such as ChatGPT. Throughout the conversation, Sword discusses practical tips and exercises for academics seeking to enhance their writing, find their voice, and rediscover the pleasures of the craft. She encourages academic writers to experiment, take risks, and trust in their ability to communicate complex ideas with clarity and style. Sword’s insights will resonate with academics across disciplines who aspire to write more engagingly, creatively, and joyfully.